Features of cognitive disorders in patients with arterial hypertension of low cardiovascular risk. - Krotova, V. Yu. (Medicni Perspektivi, 2019)
By the WHO data,Ukraineis country number1 inEuropeand number2 inthe world according to the cardiovascular mortality rate. In the structure of the prevalence of cardiovascular diseases in Ukraine, the percentage of persons of working age with arterial hypertension is 36.7%. The improvement of the prognosis of patients with arterial hypertension depends not only on long-term effective control of blood pressure, but the diagnosis and initiation of therapy at the initial stage of the development of the disease, when the target organs have not yet undergone hypertensive damage is also an important condition. The article presents the results of neuropsychological examination of 509 outpatients with a controlled second stage arterial hypertension, with an integrated assessment of cognitive functions using the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MCA) methods. It has been established that even in patients with controlled arterial hypertension stage II with a low cardiovascular risk, by SCORE scale cognitive disorders were revealed in 32,2%. The peculiarities of the development of cognitive disorders in arterial hypertension in connection with the history and course of the disease are analyzed. The majority of patients with hypertension have an increased level of anxiety, especially personality, and this is not due to the presence or absence of cognitive disorders. In patients with hypertension and cognitive disorders, on the basis of testing data by the SF-36 scale, there was a significant (p<0.001) decrease in quality of life on all scales as compared with healthy ones on average by 24.5-66.0 points.